Molecular mechanisms of lipid metabolism disorder in livers of ewes with pregnancy toxemia. (17th August 2018) - Xue, Y. F.; Guo, C. Z.; Hu, F.; Sun, D. M.; Liu, J. H.; Mao, S. Y.
Abstract : Pathogenesis of pregnancy toxemia (PT) is believed to be associated with the disruption of lipid metabolism. The present study aimed to explore the underlying mechanisms of lipid metabolism disorder in the livers of ewes with PT. In total, 10 pregnant ewes were fed normally (control group) whereas another 10 were subjected to 70% level feed restriction for 15 days to establish a pathological model of PT. Results showed that, as compared with the controls, the levels of blood β -hydroxybutyrate (BHBA), non-esterified fatty acids (NEFAs) and cholesterol were greater ( P <0.05) and blood glucose level was lower ( P <0.05) in PT ewes. The contents of NEFAs, BHBA, cholesterol and triglyceride were higher ( P <0.05) and glycerol content was lower ( P <0.05) in hepatic tissues of PT ewes than those of the controls. For ewes with PT, excessive fat vacuoles were observed in liver sections stained with hematoxylin–eosin; furthermore, inner structures of hepatocytes including nuclei, mitochondria and endoplasmic reticulum were damaged seriously according to the results of transmission electron microscope. Real-time PCR data showed that compared with the controls, the expression of hepatic genes involved in fatty acid oxidation (FAO) and triglyceride synthesis (TGS) was enhanced ( P <0.05) whereas that related to acetyl-CoA metabolism (ACM) was repressed ( P <0.05) in PT ewes. Generally, our results showed that negative energy balance altered the expression of genes involved in FAO, ACM and TGS, further caused lipid metabolism disorder in livers, resulting in PT of ewes. Our findings may provide the molecular basis for novel therapeutic strategies against this systemic metabolic disease in sheep.